2016
DOI: 10.3390/f7120316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Ectomycorrhizal Fungal Inoculates on the Growth of Pinus tabulaeformis Seedlings under Greenhouse Conditions

Abstract: Abstract:The tree species Pinus tabulaeformis Carr. (P. tabulaeformis) is commonly planted in China due to its economic and ecological value. In order to identify one or more ectomycorrhizal (ECM) fungal species for future P. tabulaeformis afforestation, we investigated the effects of five ECM fungal species: Laccaria laccata, Boletus edulis, Gomphidius viscidus, Suillus grevillei, and Suillus luteus on the growth of P. tabulaeformis seedlings under greenhouse conditions. The growth parameters of P. tabulaefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
16
2
Order By: Relevance
“…We studied the effect of ECMF and DSE inoculation on rhizosphere microbial community structure, C mic and soil enzyme activities of PWN infected P. tabulaeformis seedlings. Although ECMF inoculation can improve rhizosphere soil enzymatic activities (Lu et al, 2016), in our study, exogenous ECMF/DSE inoculation seemed to have no obvious effect on soil enzymatic activities. One explanation is that soil enzymatic activities might not be as sensitive in the relatively stable greenhouse conditions and small isolated pots as they would be in natural conditions.…”
Section: Discussioncontrasting
confidence: 74%
“…We studied the effect of ECMF and DSE inoculation on rhizosphere microbial community structure, C mic and soil enzyme activities of PWN infected P. tabulaeformis seedlings. Although ECMF inoculation can improve rhizosphere soil enzymatic activities (Lu et al, 2016), in our study, exogenous ECMF/DSE inoculation seemed to have no obvious effect on soil enzymatic activities. One explanation is that soil enzymatic activities might not be as sensitive in the relatively stable greenhouse conditions and small isolated pots as they would be in natural conditions.…”
Section: Discussioncontrasting
confidence: 74%
“…Sucrase activity was determined spectrophotometrically at 508 nm. The protease activity was determined by ninhydrin colorimetry, expressed in milligrams of amino nitrogen in 1 g of soil cultured for 24 h in a 37 °C incubator [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Their dependency on symbiosis, hosting a wide range of ectomycorrhizal fungal species [ 7 , 8 , 9 ], is advantageous for their optimal growth and development under various natural environmental conditions [ 10 ]. The symbiotic effect of ectomycorrhizal fungi is well known for improving the growth of the host plants [ 9 ] with enhanced tolerance towards environmental stresses [ 11 , 12 , 13 , 14 ]. Studies have shown that Pinus species inoculated with ectomycorrhizal fungi display improved photosynthesis, water uptake, nutrient utilization, and immune system [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%